SISTEM PENYERBUKAN ALTERNATIF Talinum triangulare Willd.: EFEK PERLAKUAN PENYERBUKAN PAD A AKTIFITAS BUNGA DAN PEMBENTUKAN BUI - Rachman, Erlin (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Eight pollination treatments were executed on Talinum triangulare Willd. to observe alternative pollination systems and its effect on some flower activities and seed setting. The treatments can be grouped to autogamy and allogamy or geitonogamy.Flowers simultaneously were treated by the eight treatments day by day for two weeks in a month with three replications.Parameters observed were fruit set, anthesis duration, seed number per capsule and presence of stigmatic curvature. The result showed that the plant species was evidently flexible in pollination systems but the plant was outcrossing species with highest seed number (58.73 ± 5.95) per capsule and did not show stigmatic lobe curvature. The second and the third highest seed number per capsule were given by natural pollination with or without anther removal and with or without artificial polination (50.5 ± 2,87 and 49.0 ± 1) and this treatments also did not showed stigmatic lobe curvature. Articial pollination with or without flower bagging, withor without anther removal and with or without natural pollination generally gave lower seed number per capsule 40.67 ± 5.69,32.67 ± 10.95, 43.67 ± 9.5) except spontan autogamy(49.29 ± 10.14) and some of this treatments showed sigmatic lobe curvature.Stigmatic lobe curvature, therefore, was occured when no pollen occupation on it until prior to naturally flower reclose. Flower would be abscised when no artificial or natural pollination was happened but its stigma was curved before shed. Primary pollination mechanism in the plant was cross polllination (allogamy) but the plant is enough flexible in pollination systems. Autogamy especially spontan autogamy seem to be alternative pollination mechanism when no natural polinator visit.